Polyelectrolyte Multilayer Films Modification with Ag and rGO Influences Platelets Activation and Aggregate Formation under In Vitro Blood Flow - Gabriela Imbir (Nanomaterials, 2020)
Surface functionalization of materials to improve their hemocompatibility is a challenging problem in the field of blood-contacting devices and implants. Polyelectrolyte multilayer films (PEMs), which can mimic functions and structure of an extracellular matrix (ECM), are a promising solution to the urgent need for functional blood-contacting coatings. The properties of PEMs can be easily tuned in order to provide a scaffold with desired physico-chemical parameters. In this study chitosan/chondroitin sulfate (Chi/CS) polyelectrolyte multilayers were deposited on medical polyurethane. Afterwards PEMs were modified by chemical cross-linking and nanoparticles introduction. Coatings with variable properties were tested for their hemocompatibility in the cone-plate tester under dynamic conditions. The obtained results enable the understanding of how substrate properties modulate PEMs interaction with blood plasma proteins and the morphotic elements.